How Gene Patents May Inhibit Scientific Research - Campo-Engelstein, Lisa; Chan, Tiffany (BioéthiqueOnline)

(untitled) (BioéthiqueOnline, 2015)
In this paper, we point out three possible ways gene patents could impede scientific research. First, gene patent laws might exacerbate the culture of secrecy ubiquitous in science. Second, gene patents may limit researchers’ ability to study poly or multigenic diseases without access to all genetic etiologies. Third, gene patents could result in a “patent thicket”.